Digital economy and economic growth research: A scientometric study of current trends and future agendas. - Chaonan, Chi; Abdul Jalil, Norasibah (Journal of Islamic, Social, Economics and Development, 2026)
In recent years, the literature on the digital economy has experienced exponential growth, with the majority of studies focusing on a single country and limited international perspectives. This paper, utilizing the Web of Science (WoS) database and employing the visualization and analysis tool known as CiteSpace (6.2.R4(64-bit) Advanced), conducts a comprehensive overview, analyzing the research landscape in the field of digital economy and economic development over the past two decades from a national perspective. The study explores current hot topics and anticipates future trends in this research domain. The findings of the study revealed that most of the publishing organizations were universities and government departments, with the most significant contributions originating from Ukraine, Russia, and China.Most of the cooperation groups are country-based, with different groups within the country, and transnational groups are almost non-existent. The main research directions for the future include the role of digital technology in sustainable development, the catalyzing impact of digital innovation on emerging industries, the influence of the digital economy on social inequality, and digital transformation.